Gallbladder Wall Thickening for Early Detection of Plasma Leakage Among Children with Dengue Fever Admitted in a Tertiary Care Hospital - Khanam, Morsheda; Ferdoucy, Sultana Amena; Rahat, Farhana; Iman, Kazi; Moshaed Hossain, Riad Mohammad; Chowdhury, Ahmed Murtaza (Bangladesh Journal of Child Health, 2024)
Background: Plasma leakage is defined as e”20% elevation of hematocrit from baseline or evidence of plasma leakages such as pleural effusion, ascites, or hypoalbuminemia. In the early phase, these signs of plasma leakage are usually difficult to ascertain by physical examination and laboratory tests. Objective: This study aimed to investigate whether gallbladder wall thickening (GBWT) in the febrile phase of the disease can be used to detect the occurrence of plasma leakage in dengue patients. Methods: A cross-sectional analytical study was conducted during a 4-month period in Dr. M R Khan Shishu Hospital and ICH from September 2021 to December 2021. Children from 6 months to 14 years who were admitted with acute onset of fever less than 3 days with NS1 positivity were included consecutively. Laboratory tests and abdominal Ultrasonography were also performed to confirm the occurrence of plasma leakage. Result: Out of 114 patients, the majority were male (64%), in the 5-<10-year age group(48.25%). Common presentations include fever (100%), flushed appearance (66.7%), abdominal pain (66.7%), vomiting (44.7%), bodyache (39.5%), During the febrile phase, 56patients were presented with GBWT, 49 of which showed plasma leakage during treatment. The sensitivity and specificity of GBWT during fever were 89% and 88%. PPV and NPV were 87% and 90% respectively. In risk factor analysis, Gallbladder wall thickening was found statistically significant (<.009) predictor of plasma leakage in dengue. Conclusion: Gallbladder wall thickening during the febrile phaseis a predictor of plasma leakage in Dengue. BANGLADESH J CHILD HEALTH 2022; VOL 46 (3) : 138-143